Immediate implant placement in extraction sockets using i-PRF–enhanced bone grafts and amniotic membrane with zirconia crown rehabilitation: A clinical and digital radiographic evaluation - Swapnaneel Pradhan (Bioinformation, 2026)
Immediate implant placement remains challenged by marginal bone loss and peri-implant soft tissue instability despite its clinical advantages. Therefore, it is of interest to evaluate the effectiveness of i-PRF–enhanced bone grafts combined with amniotic membrane in 100 patients undergoing immediate implant placement and zirconia crown rehabilitation. Patients receiving i-PRF, bone graft and amniotic membrane showed significantly better plaque index, gingival index, probing depth, implant stability and marginal bone preservation than those receiving bone grafts alone (p < 0.05). The adjunctive use of i-PRF and amniotic membrane improved both clinical and radiographic outcomes during the 6-month follow-up period. Thus, combining i-PRF with amniotic membrane may enhance peri-implant tissue regeneration and implant stability, improving the predictability of immediate implant therapy.